Jawi using multi-maker augmented reality - Siti Hasnah Tanalol; Dinna N. Mohd Nizam; Zaidatol Haslinda Abdullah Sani; Aslina Baharum; Asni Tahir; Iznora Aini Zolkifly (Bulletin of Electrical Engineering and Informatics, 2021)
This paper discussed the development of multi-maker augmented reality for learning Jawi in order to complement the formal study in school. We conducted an experiment with N=10 participants from Pusat Minda Lestari, UMS age 5 and 6 years old, to study the effectiveness of learning Jawi using the developed mobile augmented reality application. We prepared a test environment comprising an electroencephalography (EEG) system and mobile augmented reality (AR) application for analysis and testing. Results found that the learn ability of the students was improved after they used the mobile application to learn basic Jawi. The methodology used was ADDIE model, which included the analysis, design, development, implementation, and evaluate phases. This project is an innovation in learning Jawi and hopefully can increase the children’s interest in learning Jawi.